How Can Every Organization Manage the Operational Risk? - Ferry Jie; Hasan Akpolat; Deepak Sharma; James Irish (The Winners, 2002)
This article describe how every organization (generally) and Australian Organizations (specifically) can manage the operational risks.  Recently, the operational risks are the significant issues in every organization because every organization will suffer from poor operational performance due to risks, failure, and problems such as a number of losses which are likely to be made worse. Basically, the operational risk management process has five steps, identification, analysis, treatment, controlling, and communication/consulting. Generally, many organizations (in particularly in Australia and New Zealand) have already used AS/NZS 4360-Risk Management System, AS/NZS 4801-Occupational Health and Safety Management System, ISO 14001: Effective Environmental Management System, ISO 9001: Quality Management System, AS/NZS 7799: Information Security Management, AS/NZS 3806: Compliance Management System for reducing/mitigating/managing the operational risks. Based on the SAI Certification Register, the number of Australian Organizations got the AS/NZS ISO 9000 series, AS/NZS 14000 series, AS/NZS 4801 and AS/NZS 7799.2:2000 Certifications are 3338, 30, 20 and 5 respectively. It can conclude that Australian Organizations prefer used AS/NZS ISO 9000 series rather than AS/NZS ISO 14000 series, AS/NZS 4801 and AS/NZS 7799.2:2000.